New Masculinities as Prevention and Resistance to Violence Against Women - Arif Wafidhi (Journal of Feminism and Gender Studies, 2023)
Abstract Violence against women does not arise in an empty space. Violence against women emerges as a consequence of the construction of dominant masculinity that has been maintained for thousands of years. Long history bears witness to how this construction continues to produce a dominant-subordinate position between men and women. Men in the dominant position and women in the subordinate position. This article discusses the history of masculinity from traditional-modern-postmodern and tries to criticize the masculinity of each period. The analytical tool used is a compilation of critical social theory in Ben Agger's book and Janet Saltman Chafetz's theory of masculinity hegemony. The method used is the literature study method, to trace how the evolution of masculinity that was originally rigid has now become more fluid. The result of this article is how new men who are the product of postmodern masculinity can be used as a concept to prevent and fight violence against women. This concept is known as the new masculinity. Keywords : Violence, History, New Masculinity, Women, and Resistance